Photocurrent Enhancement in Diketopyrrolopyrrole Solar Cells by Manipulating Dipolar Anchoring Terminals on Alkyl‐Chain Spacers. Issue 3 (18th December 2013) - Tang, Ailing; Lu, Zhenhuan; Bai, Shuming; Huang, Jianhua; Chen, Yuxia; Shi, Qiang; Zhan, Chuanlang; Yao, Jiannian
Abstract We chose DPP‐BDT‐DPP DPP=diketopyrrolopyrrole, BDT=4, 8‐di‐[2‐(2‐ethylhexyl)‐thienyl]benzo[1, 2‐b:4, 5‐b′]dithiophene as a model backbone and varied the anchoring groups [C5H11, COOCH3, and SiCH3(OSiCH3)2] terminated on the N‐substituted alkyl‐chain spacer of the DPP units to study the effect of anchoring terminals on the morphology of blend film and on the device performances of bulk heterojunction solar cells. By replacing the nonpolar C5H11 anchoring terminal with the polar COOCH3 anchoring terminal leads to an enhancement in the short‐circuit current density (Jsc) (4.62 vs. 9.32 mA cm−2), whereas the value of Jsc sharply decreases to 0.45 mA cm−2 if the C5H11 anchoring terminal is replaced by a SiCH3(OSiCH3)2 group. The changes in Jsc are associated with changes in the π–π stacking distance (3.39→3.34 Å vs. 3.39→3.45 Å) and the phase size (50→20 nm vs. 50→>250 nm) through alteration of the anchoring group from C5H11 to COOCH3 versus from C5H11 to SiCH3(OSiCH3)2. Interestingly, the anchoring terminals bring about drastic changes in molecular orientations, which result in different out‐of‐plane hole transport. This is the first time this effect has been systemically demonstrated to improve photocurrent generation by manipulating the dipolar anchoring groups terminated on the alkyl‐chain spacer.